ANALISIS KINERJA KEUANGAN MANCHESTER UNITED PLC SEBELUM DAN DI MASA PANDEMI COVID-19 - Suparna Wijaya; Tubagus Fathul Rizki Khoironi (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2021)
This study aims to compare the factors that affect financial performance between Manchester United Plc and the similar industries by examinating financial ratios trends before and during the Covid-19 pandemic. The object under study was the Manchester United football club, while the industry average used the six biggest football clubs in the English Premier League, such as Arsenal, Chelsea, Liverpool, Manchester City, Manchester United, and Tottenham Hotspur. This study used a literature study method by collecting relevant data and information according to the topics discussed through various literatures. In addition, this study also using financial ratio indicators that were applied to the football industry to measure the financial performance of a football club. The data used were secondary data in the form of company financial statements from 2018 to 2020 from the company's official website. The results of this study conclude that Manchester United's financial performance tends to decrease,, especially in profitability due to the postponement of the competition during the Covid-19 pandemic. On the other hand, Manchester United's financial performance was stated to be good in terms of efficient management of employee payroll expenses and sponsorship contract revenues. Therefore, investors need to review the condition of football clubs based on financial ratios before making investment decisions on football clubs.